Encontros-narrativas na cidade-internação : vidas contadas por adolescentes em cumprimento de medida socioeducativa - Batista, Ruth (2012)
This dissertation search occurred in the Institute of Socio-Educational Services at the State of Espírito Santo – IASES, body responsible for implementation of educational measures to adolescents who practice illegal acts. It had focus on the measure of detention served in the Social Inpatient Unit – UNIS. As established in the Statute of the Child and Adolescent (ECRIAD) and the National System of Social and Educational Care (SINASE), such measures should promote pedagogical practices guided on the shaft (education) and not in the axis of sanctions (punitive). The dissertation search here discussed, with adolescents in daily inpatient unit, revealed the multiplicity of relationships, practices, the threads that weave the social and educational care, imposing the need for methodological tools that would allow evidence such methodological variation of compositions with the micro-relations, the micro- confrontations caught in this context. The field diary, produced along our inclusion as a worker and researcher, as the technique of narrative power, the meetings and their affectations were betting our ethical and political practices that promoted the understanding, modes of operation of the institution and the relations of knowledge/power there evidenced. We pursue, in the meetings-narratives with the adolescents and diving into the field, not the path marked by the system, but other walk trails possible. Prioritize finding deviations, escapes control, production alliances and new ways of being and belonging to the world. The tales-narratives are the results of the meeting. Are ways of telling which show the offal of the stories told and lives lived.